Greenhouse Gas Mitigation in Forest and Agricultural Lands: Reducing Emissions - Solomon G. Haile; Clyde W. Fraisse; Ramachandran P-K Nair; Vimala D. Nair (EDIS)
AE443, a 7-page fact sheet by Solomon G. Haile, Clyde W. Fraisse, P.K. Ramachandran Nair, and Vimala D. Nair, is part of the Greenhouse Gas Mitigation in Forest and Agricultural Lands series. It provides basic information about greenhouse gases (GHGs), the greenhouse effect, and global warming, and sources of GHG emissions from forest and agricultural lands and discusses land management practices that have potential to reduce GHG emissions in the agricultural and forestry sectors of Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, December 2008.